(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2015)
The accounting and analytical support for the process of the forecasting formation in the strategic planning. Forecasting is a prerequisite for forming relevant strategic goals of the company and correcting existing strategies in the process of their implementation. The principles of forecasting have been identified in the article for the purpose of the strategic planning with the release of the tasks of the accounting and analytical support. The structure of the system of the accounting and analytical support forecasting has been examined. The strategic planning data have been systematized